Narrativas para a cidade: sobre a formação e os usos do patrimônio cultural em Diadema - Sancho, Lindolfo Campos [UNIFESP] (2019)
Since the beginning of the 1990’s, a set of actions have been taken to identify and protect Diadema’s cultural heritage. Led by a few city hall employees, distinct concepts and methods related to the cultural heritage area have been implemented on this local context, resulting in the publication, in 2015, of a municipal decree establishing an inventory of cultural goods. This inventory is this dissertation’s main object of study where we seek to identify, through both the inventory and its formulation process, concepts linked to cultural heritage and methods applied to identify it that result in specific ways of understanding the city. Once having identified these concepts and methods, we expect to be able to make explicit the ways in which the idea of “cultural heritage” is mobilized as a tool to organize the territory on a symbolic level, as well as its uses on our daily lives.